The Effect of Employees’ Personal Characteristics and Organizational Climate on Organizational Performance, with regard to the Mediating Role of Organizational Knowledge Creation Process (Case Study of Paxan Co (LLP)) - Mohammad Taghi Taghavifard; Jalal Rezaee Noor; Mehdi Seyfollahi; Narges Aghakhani (مدیریت مهندسی و رایانش نرم)
The process of organizational knowledge creation is affected by various individual (attitudes and motivation) and organizational factors (Organizational culture, leadership style and organizational structure). The process of knowledge creation requires people (attitude and motivation) and collaborative atmosphere (the desired organizational climate). Organizational climate and individual characteristics are two major factors to improve organizational performance. In the previous studies, the effects of organizational climate, and those of motivation and attitude on organizational performance have been investigated separately. This study has investigated the simultaneous effects of these two variables on organizational performance, as well as the mediating role of the process of organizational knowledge creation and is considered creative with this regard. This research is a descriptive coorelational study, in which structural equation modeling (SEM) is used. Data collection was done using questionnaires. In order to assess the reliability of questionnaires, Cronbach's alpha has been calculated. The results show that organizational climate and individual characteristics have a positive and significant effect on the process of knowledge creation. In addition, the process of organizational knowledge creation, as a mediator variable, has a significant role in the influenceability of organizational climate and individual characteristics in organizational performance.